Cross-cultural perspectives on the patient-provider relationship: a qualitative study exploring reflections from Ghanaian medical students following a clinical rotation in the United States. Issue 1 (December 2015) - Abedini, Nauzley; Danso-Bamfo, Sandra; Kolars, Joseph; Danso, Kwabena; Donkor, Peter; Johnson, Timothy; Moyer, Cheryl
Abstract Background In international health experiences, learners are exposed to different culturally-based patient care models. Little is known about student perceptions of patient-provider interactions when they travel from low-to high-resource settings. The purpose of this study was to explore these reflections among a subset of Ghanaian medical students who participated in clinical rotations at the University of Michigan Medical School (UMMS). Methods In-depth, semi-structured interviews lasting 60–90 min were conducted with 15 individuals who had participated in 3-to 4-week clinical rotations at UMMS between January 2008 and December 2011. Interviews were conducted from March to August 2012 and transcribed verbatim, then independently coded by three investigators. Investigators compared open codes and reached a consensus regarding major themes. Results Participating Ghanaian medical students reported that their perspectives of the patient-provider relationship were significantly affected by participation in a UMMS rotation. Major thematic areas included: (1) observations of patient care during the UMMS rotation, including patient comfort and privacy, physician behavior toward patients, and patient behavior; (2) reflections on the role of humanism and respect within patient care; (3) barriers to respectful care; and (4) transformation of student behaviors and attitudes. Students also reported integrating more patient-centered care into their own medical practice upon return to Ghana Discussion Participation in a US-based clinical rotation has the potential to introduce medical students from resource-limited settings to a different paradigm of patient-provider interactions, which may impact their future behavior and perspectives regarding patient care in their home countries. Conclusions Students from under-resourced settings can derive tremendous value from participation in clinical electives in more affluent settings, namely through exposure to a different type of medical care.